SOUNDCLOUD UTILISATION AS A TOOL FOR STUDENTS IN PRESENTING ORAL BOOK REVIEW - Vega Hesmatantya (Siliwangi University, 2018)
The use of technology in education is significantly growing. Some research findings present a huge improvement in the evolution of teaching and learning activities. English teaching in Indonesia has many challenges since English, as a foreign language, requires innovative teaching strategies, tools and media. This paper attempts to investigate how SoundCloud, an online audio distribution platform, could be utilised in English language teaching. It is applied in Extensive English class where students present their oral book reviews. The data collections were obtained from questionnaire and teacher’s observation on students’ oral book review on SoundCloud. Each student was assigned to read a book, report it orally, and upload it on SoundCloud, while the other students listen and leave comment on it. The finding showed that it was easy for them to operate SoundCloud. Therefore, it created fun learning and encouraged students to learn how to communicate book review orally and listen well to other student’s review. Thus, according to the finding, it is recommended for the upcoming study to explore more on the use of SoundCloud in other ELT activities.